The Basics of Agricultural BMPs in Northern Florida and Southwestern Georgia: FOR368/FR437, 6/2021 - Monroe, Martha C.; Barrett, Charles E. (EDIS, 2021)
Best management practices (BMPs) are cost-efficient processes that improve daily life, from healthcare to food service. Agricultural BMPs aim to reduce water use and improve water quality and soil on farms and ranches as well as to encourage better forestry practices and lawn care. This fact sheet introduces non-farmers to agricultural BMPs.